The ceramic heritage on the Nicoya Peninsula: Persistence of a tradition - Weil, Jim (2014)
Documentation of the manufacture of three types of ceramic pieces in San Vicente de Nicoya supports inferences about continuities and changes in raw materials, tools, techniques, organization of work, styles and uses. The findings serve the purposes of archaeologists, historians and ethnologists looking for elements of ancient and more recent artisan traditions which still are practiced in the present. Such interdisciplinary research contributes to the preservation and reinforcement of the local cultural heritage.